High-quality tar production from coal in an integrated reactor: Rapid pyrolysis in a drop tube and downstream volatiles upgrading over char in a moving bed. (1st February 2021) - Wang, Demin; Chen, Zhaohui; Li, Changming; Wang, Deliang; Li, Yunjia; Yang, Hang; Liu, Zhouen; Yu, Jian; Gao, Shiqiu
Highlights: An integrated reactor was developed to combine coal rapid pyrolysis and volatiles upgrading. Rapid pyrolysis in the upper drop tube guaranteed the high-yield production of tar. Combining volatiles upgrading in the lower moving bed improved the tar quality. The degree of volatile-char interaction could be controlled by temperature and char bed thickness. Combining rapid pyrolysis and volatiles upgrading achieved the high-quality tar production from coal. Abstract: A purposely built integrated reactor, which comprised a drop tube and a moving bed assembly located at the bottom of the drop tube, combined rapid pyrolysis and in situ volatiles upgrading over char for the production of high-quality tar from coal. Rapid pyrolysis took place when coal particles flowed through the hot drop tube, and then the produced volatiles and char were introduced into the moving bed for further pyrolysis and volatiles upgrading. The operation parameters of rapid pyrolysis alone in the drop tube were first investigated to ensure a high yield of the initial tar for further upgrading in the moving bed. The effects of the temperature and char bed thickness on further pyrolysis and volatiles upgrading were then determined to obtain the optimized operating conditions in the moving bed. Under the optimized conditions, the tar yield could be as high as 11.4 wt% and reached 89.8% of the Gray-King assay yield. The light fraction in the tar and light tar yield reached 69.0% and 7.9 wt%, respectively, which was much better than that obtained from the rapid pyrolysis alone in the drop tube. The experimental results could confirm the feasibility of the integrated pyrolysis-upgrading process for the production of high-quality tar from coal.